Prevalence of metabolic syndrome among obese diabetic subjects - Mehwish Zeeshan; Muhammad Imran; Humaira Jabeen; Sumreen Begum; Nazia Ahmed; Rashida Qasim (International Journal of Endorsing Health Science Research, 2015)
Background: Metabolic syndrome (MS) is a cluster of metabolic risk factors including obesity, glucose intolerance, insulin resistance, dyslipidemia and hypertension. MS in obese and type 2 diabetic (T2DM) subjects increases the risk of cardiovascular diseases (CVD). The objective of the present study is to estimate the prevalence of MS in obese T2DM subjects by using International Diabetes Federation (IDF) and National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III) definitions.